(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This study explores the methodological features of developing creative and analytical thinking in students through the use of quest-based technology in the educational process. The quest technology approach encourages learners to interact actively with educational material by solving problem-oriented tasks in a game-like environment. It strengthens motivation, fosters independent thinking, and creates situations that require making decisions based on analysis, comparison, and synthesis of information. The integration of quests into lessons not only enhances cognitive engagement but also allows students to apply theoretical knowledge in practical contexts. As a result, learners demonstrate improved creativity, reflectivity, teamwork skills, and the ability to formulate and defend their viewpoints logically.